Osip Mandel'štams "Egipetskaja marka" Eine Rekonstruktion der Motivsemantik - Bonola, Anna (Slavistische Beitraege, 1995)
The present work reconstructs the motif semantics of the story "Egipetskaya Marka" by Osip Mandel'štam, taking into account both the entire older text corpus and the intertextual slide mentioned in the narrative.